Tinjauan Yuridis Peraturan Presiden Nomor: 5 Tahun 2025 tentang Satuan Tugas Penertiban Kawasan Hutan Berhubungan dengan Hak Masyarakat Hukum Adat dan Tanah Milik di Kawasan Hutan - Fakhry Firmanto (Jurnal Hukum Lex Generalis, 2026)
This research critically examines Presidential Regulation Number 5 of 2025 regarding the Forest Area Discipline Task Force and its impact on Indigenous Law Communities and private landholders. Through philosophical, sociological, and juridical lenses, the study analyzes the tension between state-led "discipline" and constitutional rights. Findings suggest that the regulation risks prioritizing formalistic mapping over substantive justice, potentially violating the landmark Constitutional Court Decision No. 35/PUU-X/2012. Furthermore, it identifies a deficit in legal certainty for titled landholders. The study recommends a restorative approach, integrating rights verification and participatory mapping to ensure that forest governance harmonizes with agrarian justice and human rights.